A Nanographene‐Based Two‐Dimensional Covalent Organic Framework as a Stable and Efficient Photocatalyst. (16th December 2021) - Jin, Enquan; Fu, Shuai; Hanayama, Hiroki; Addicoat, Matthew A.; Wei, Wenxin; Chen, Qiang; Graf, Robert; Landfester, Katharina; Bonn, Mischa; Zhang, Kai A. I.; Wang, Hai I.; Müllen, Klaus; et al.
Abstract: Synthesis of covalent organic frameworks (COFs) with desirable organic units furnishes advanced materials with unique functionalities. As an emerging class of two‐dimensional (2D) COFs, sp 2 ‐carbon‐conjugated COFs provide a facile platform to build highly stable and crystalline porous polymers. Herein, a 2D olefin‐linked COF was prepared by employing nanographene, namely, dibenzo[ hi, st ]ovalene (DBOV), as a building block. The DBOV‐COF exhibits unique ABC‐stacked lattices, enhanced stability, and charge‐carrier mobility of ≈0.6 cm 2 V −1 s −1 inferred from ultrafast terahertz photoconductivity measurements. The ABC‐stacking structure was revealed by the high‐resolution transmission electron microscopy and powder X‐ray diffraction. DBOV‐COF demonstrated remarkable photocatalytic activity in hydroxylation, which was attributed to the exposure of narrow‐energy‐gap DBOV cores in the COF pores, in conjunction with efficient charge transport following light absorption. Abstract : Dibenzo[ hi, st ]ovalene‐based covalent organic frameworks form 2D ABC stacking sp 2 carbon lattices with robust olefin linkage. The resulting 2D unique structure exhibits high photoconductivity, charge‐carrier mobility and photocatalytic activity in hydroxylation attributed to the narrow‐energy‐gap nanographene cores as active sites.